Identifying the ideal body size and shape characteristics associated with children's physical performance tests in Peru - Bustamante Valdivia, A.; Maia, J.; Nevill, A. (Scandinavian journal of medicine & science in sports, 2015)
We used allometric models to identify the optimal body size/shape characteristics associated with physical and motor performance tests in Peruvian schoolchildren. The sample consisted of 3624 subjects (1669 boys and 1955 girls) aged 11–17 years from 31 public schools belonging to four cities located in the three natural regions in central Peru. Motor performance included 12‐min run, standing long jump, grip strength, curl‐ups, shuttle run, and sit and reach. The reciprocal Ponderal index (RPI), a characteristic sometimes referred to as the somatotype “ectomorphy,” was found to be the most suitable body shape indicator associated with 12‐min run, standing long jump, curl‐up, and shuttle run performance. A positive maturation offset parameter was also associated with greater standing long jump, grip strength, shuttle run, and sit‐and‐reach performances. With the exception of the sit‐and‐reach flexibility, sex differences are pervasive in all tests favoring boys. Rainforest schoolchildren are best performers in the power and flexibility tests, whereas those from high altitude were superior in the 12‐min endurance test even after taking their much lighter body size characteristics into account. This latter finding suggests that living at high altitude in Peru benefits children's endurance performance both before and even after controlling for differences in the confounding variable of body size/shape.